How celebrity involvement affect destination image, the mediating role of celebrity worship - Shelvina; Fitriana Aidnilla Sinambela; Fahlevi, Renza (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
The film industry plays a significant role in influencing tourists' travel destination choices. This study aims to explore the relationship between celebrity involvement and destination image, with celebrity worship serving as a mediating variable. This research depicted the case of Chinese film industry to examines how films and celebrities impact destination image. This research uses quantitative research methods with the PLS-SEM research model. the study surveyed 310 Batam residents who have watched Chinese movies or TV series. The findings indicate a positive and significant relationship between celebrity involvement and destination image, mediated by celebrity worship.